DATA AVAILABILITY IN DECENTRALIZED DATA STORAGE USING FOUR-NODE INTERPLANETARY FILE SYSTEM - Tony Haryanto; Kalamullah Ramli; Arga Dhahana Pramudianto (Jurnal Teknik Informatika (Jutif), 2023)
Centralized storage is a data storage model in which data is stored and managed in a single physical location or centralized system. In this model, all data and information are stored on servers or data centers managed by one entity or organization. This model also has disadvantages such as risk of system failure against distributed denial of service (DDoS) attacks, natural disasters, and hardware failures causing a single point of failure. This threat results in loss of data and a lack of user confidence in the availability of data in centralized storage. This study proposes to evaluate the availability of data in decentralized data storage using a four-node interplanetary file system (IPFS) that is interconnected with a swarm key as the authentication key. Unlike centralized storage which has only one data center, four-node IPFS allows users to upload and download data from four interconnected data centers. This can avoid dependence on the central server and reduce server load. The evaluation results show that decentralized data storage using a four-node IPFS system is three times more resilient than centralized storage against a single point of failure. This system can increase data availability so that organizations can minimize data loss from the threat of system failure.